The IDA Peptide Controls Abscission in Arabidopsis and Citrus - Estornell, Leandro H.; Wildhagen, Mari; Pérez-Amador, Miguel A.; Talón, Manuel; Tadeo, Francisco R.; Butenko, Melinka A. (Frontiers in Plant Science, 2015)
Organ abscission is an important process in plant development and reproduction. During abscission, changes in cellular adhesion of specialised abscission zone (AZ) cells ensure the detachment of infected organs or those no longer serving a function to the plant. In addition, abscission also plays an important role in the release of ripe fruits. Different plant species display distinct patterns and timing of organ shedding, most likely adapted during evolution to their diverse life styles. However, it appears that key regulators of cell separation may have conserved function in different plant species. Here we investigate the functional conservation of the citrus orthologue of the Arabidopsis peptide ligand INFLORESCENCE DEFICIENT IN ABSCISSION (AtIDA), controlling floral organ abscission. We discuss the possible implications of modifying the citrus IDA orthologue for citrus fruit production.